The roads ahead: Saga of highway development in India - Nautiyal, Santosh (2004)
The last decade has witnessed a massive activity in the road network development in the country. Realising the importance of fast and well-constructed roads for development, the National Highway Authority has been entrusted to construct and develop about 25,000 km of National Highways. This article unfolds the details of the schemes and projects being undertaken by authority to provide a networked life-line for the overall development of the country. - Reproduced.
Keywords: Roads - India; Roads